Gender differences in reading: Examining text-based interest in relation to text characteristics and reading comprehension. (December 2022) - Lepper, Chantal; Stang-Rabrig, Justine; McElvany, Nele
Abstract: Reading is a key competence for knowledge acquisition and learning processes. One important source of reading motivation is interest. Even though students' text-based interest often differs by gender, it remains unclear which text factors underlie these differences and whether text-based interest relates to reading comprehension among boys and girls. In a sample of 514 elementary students (47.2% girls), this study examined whether text topic, protagonists' gender, and text difficulty affect boys' and girls' text-based interest and whether interest and reading comprehension are intertwined. Based on a repeated within-subject design using fourteen narrative texts, the results indicated that boys' interest was higher in texts with male-attributed topics, male protagonists, and in more difficult texts. In contrast, girls' interest was only affected by text difficulty. Text-based interest and reading comprehension were significantly related, albeit stronger for boys than for girls. The findings are discussed regarding future implications for research and educational practice. Highlights: Female topics and female protagonists predicted boys' text-based interest negatively. Girls' and boys' text-based interest varied based on text difficulty. Children's interest in a text was positively related to reading comprehension. Interest and reading comprehension were stronger associated for boys than for girls.